2013
DOI: 10.1152/ajprenal.00546.2012
|View full text |Cite
|
Sign up to set email alerts
|

Renal uptake of the antiapoptotic protein survivin is mediated by megalin at the apical membrane of the proximal tubule

Abstract: The inhibitor of apoptosis protein survivin is a bifunctional molecule that regulates cellular division and survival. We have previously shown that survivin protein can be found at high concentrations in the adult kidney, particularly in the proximal tubules. Here, survivin is localized primarily at the apical membrane, a pattern that may indicate absorption of the protein. Several proteins in primary urine are internalized by megalin, an endocytosis receptor, which is in principle found in the same localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Surprisingly, the mRNA expression of survivin was increased, but survivin protein was reduced by UUO, irrespective of the mouse genotype. This might be due to the fact that survivin protein is primarily regulated via tubular uptake from the primary urine and not via expression by renal cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the mRNA expression of survivin was increased, but survivin protein was reduced by UUO, irrespective of the mouse genotype. This might be due to the fact that survivin protein is primarily regulated via tubular uptake from the primary urine and not via expression by renal cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…105 In addition, megalin has been shown to mediate the uptake of endogenous substances that may be involved in modulation of and recovery from AKI, [106][107][108] including NGAL 109 and survivin. 110 So far no studies have established the functional importance of either megalin or cubilin for the progression of AKI. It is, however, intriguing that changes in megalin expression have been identified in a time-dependent manner in AKI, leading to the speculation that megalin may play a dual role in AKI, initially being involved in progression but, with time, eventually also playing a role in recovery by the clearance of cellular debris and tubular, endocytic uptake of filtered substances, such as NGAL, important for cellular protection.…”
Section: Role Of Megalin-mediated Protein Uptake In Progression Of Acmentioning
confidence: 99%
“…NGAL has been shown to bind megalin (32), and the localization of filtered NGAL in late endosomes and lysosomes during I/R in mice suggests that megalin mediates uptake into PTECs (53,56) and thus is important for the observed renoprotective effect. Other proteins that have been shown to bind to megalin, such as L-FABP, clusterin, and survivin (34,42,63), may also have renoprotective effects in AKI. This has been demonstrated in L-FABP-overexpressing mice exposed to ischemia, cisplatin, or aristolochic acid (51,59,92).…”
Section: Megalin In Akimentioning
confidence: 99%
“…Survivin is expressed in the heart, brain, liver, lung, and kidney, where it regulates cell division and survival (2). Filtered survivin binds to megalin, mediating proximal tubule uptake (34), and is also known to be expressed in PTECs under normal physiological conditions (46). Studies using kidney-specific survivin deletion have shown that survivin increases the functional and structural recovery of PTECs after I/R injury in mice (14) and reduces tubular injury (39) in cisplatin-induced AKI.…”
Section: Megalin In Akimentioning
confidence: 99%